Synthesis of Pr0.6Sr0.4FeO3−δ–xCe0.9Pr0.1O2−δ cobalt-free composite cathodes by a one-pot method for intermediate-temperature solid oxide fuel cells. (19th February 2016) - Jin, Chao; Mao, Yachun; Rooney, David W.; Sun, Wang; Zhang, Naiqing; Sun, Kening
Abstract: Cobalt-free composite cathodes consisting of Pr0.6 Sr0.4 FeO 3−δ – x Ce0.9 Pr0.1 O 2−δ (PSFO- x CPO, x  = 0–50 wt%) have been synthesized using a one-pot method. X-ray diffraction, scanning electron microscopy, thermal expansion coefficient, conductivity, and polarization resistance ( R P ) have been used to characterize the PSFO- x CPO cathodes. Furthermore the discharge performance of the Ni-SSZ/SSZ/GDC/PSFO- x CPO cells has been measured. The experimental results indicate that the PSFO- x CPO composite materials fully consist of PSFO and CPO phases and posses a porous microstructure. The conductivity of PSFO- x CPO decreases with the increase of CPO content, but R P of PSFO-40CPO shows the smallest value amongst all the samples. The power density of single cells with a PSFO-40CPO composite cathode is significantly improved compared with that of the PSFO cathode, exhibiting 0.43, 0.75, 1.08 and 1.30 W cm −2 at 650, 700, 750 and 800 °C, respectively. In addition, single cells with the PSFO-40CPO composite cathode show a stable performance with no obvious degradation over 100 h when operating at 750 °C. Graphical abstract: Highlights: Pr0.6 Sr0.4 FeO3−δ –xCe0.9 Pr0.1 O2−δ (x = 0–50 wt%) were prepared by a one-pot method. The Gd0.1 Ce0.9 O1.95 interlayer was attained by a spin-coating method. Pr0.6 Sr0.4 FeO3−δ –40Ce0.9 Pr0.1 O2−δ exhibits the lowest polarization resistance. The discharge performance of cell with Pr0.6 Sr0.4 FeO3−δ –40Ce0.9 Pr0.1 O2−δ is optimal.